Search for the X(5568) State Decaying into B-s(0)pi(+/-) in Proton-Proton Collisions at root s=8 TeV - Sirunyan, A. M. (2018)
A search for resonancelike structures in the B-s(0)pi(+/-) invariant mass spectrum is performed using proton-proton collision data collected by the CMS experiment at the LHC at root s = 8 TeV, corresponding to an integrated luminosity of 19.7 fb(-1). The B-s(0) mesons are reconstructed in the decay chain B-s(0) -> J/Psi phi, with J/Psi -> mu(+) mu(-) and phi -> K+K-. The B-s(0)pi(+/-) invariant mass distribution shows no statistically significant peaks for different selection requirements on the reconstructed B-s(0) and pi(+/-) candidates. Upper limits are set on the relative production rates of the X(5568) and B-s(0) states times the branching fraction of the decay X(5568)(+/-) -> B-s(0)pi(+/-). In addition, upper limits are obtained as a function of the mass and the natural width of possible exotic states decaying into B-s(0)pi(+/-).